Digitalization in Mycelia Forest Management, Cikole Village: Innovative efforts towards sustainable tourism - Desy Nur Aini Fajri; Intan Pratiwi (Borneo Novelty Publishing, 2025)
Purpose - This research elaborates on innovative efforts to develop Mycelia Forest in Cikole Village using digital information technology. It aims to explore how digital technology can be leveraged to foster sustainable tourism in the area. Methodology/Design/Approach - A descriptive qualitative approach was used in this study. Data were collected through in-depth interviews, observation, and documentation. The analysis followed three stages: data reduction, data presentation, and conclusion drawing.Finding - The study identified three key innovative digitalization efforts that are effective in developing Mycelia Forest for sustainable tourism: (1) Deploying digital information technology media, (2) Elevating accessibility and service quality, and (3) Building cooperation with diverse stakeholders. These efforts help improve both the management and promotion of the forest as a tourist destination. Originality/Value - The research provides new insights into how digital information technology can support the management and promotion of tourist destinations, particularly tourist forests, contributing to their sustainable development.